Trends in the Economic Condition in the Conditions of the Recovery of Economic Activity - Zaynalov Jahongir Rasulovich; Aziza Tokhirovna Akhmedova (International Journal on Economics, Finance and Sustainable Development, 2022)
The article reveals the features of the trends in the development of the economic conjuncture as part of the revival of economic activity, outlines the features of economic recovery, accompanied by an investment boom in the conditions of the revival of the economy of Uzbekistan on a new basis, determines the mechanism for choosing an investment strategy, the pace and efficiency of investments, their payback.